PENGUATAN POSITIF GURU DALAM UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA KOMPETENSI DASAR HUBUNGAN SATUAN PANJANG MATEMATIKA KELAS IV SD NEGERI 060883 MEDAN PETISAH - Jojor Silaban (FIP Unimed, 2019)
ABSTRACTStudent achievement motivation will increase if given positive reinforcement in the form of prizes in learning mathematics in Class IV SD60603 Medan Petisah. The population of this study was conducted on all Class IV students at 060883 Medan Petisah Primary School. A total of 44 people, using positive reinforcement (prizes). This research was conducted in the subject area of Mathematics Subject